Pembuatan Website untuk Rekomendasi Smartphone - Bryan Christiansen; Leo Willyanto; Hans Juwiantho (Jurnal Infra, 2020)
The era of digitalization is upon mankind. Humans as a social being are heading towards a faster way of exchanging information. With all accessible information known to man is on our fingertip, the use of gadgets is no longer a luxury, but becomes a necessity.The topic for this thesis is creating a website that can give those who need to buy smartphone but do not understand the details of difference of each product. Recommendations that are given to the user are based on their preferences like price or the size of the smartphone. The website converts the criteria of preferences that are inputted by the user into  more detailed parameters.The result of this thesis can give users a list of smartphones recommendations. Via the list given, user can have a new perspective and options that are small in size to choose a smartphone that matches user’s criteria of preferences.